Urgensi Apersepsi Dalam Mengasah Critical Thinking Siswa SD Bermuatan Profil Pelajar Pancasila - Ananda Zahrotun Nisa; Eny Stiyowati; Maria Maskanah; Muhammad Nofan Zulfahmi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Apperception activities have an important role in building the foundation for critical thinking in elementary school students, especially in supporting the Pancasila Student Profile. This research aims to explore the urgency of implementing well-designed apperception in encouraging students' critical thinking abilities. This research uses the library research method as the main approach for collecting and analyzing data. Library research is a qualitative research method that does not involve direct field activities, but focuses on collecting information from various written sources, both published and unpublished. The research results show that structured apperception activities can effectively increase students' active involvement, connecting previous knowledge with new concepts, and gradually forming a critical thinking pattern. This study provides valuable insight for educators in designing effective and targeted learning strategies, which emphasize the development of critical thinking skills from an early age.